A cluster analysis of high-performance handball players' perceived motivational climate: Implications on motivation, implicit beliefs of ability and intention to be physically active. Issue 4 (August 2019) - Gómez-López, Manuel; Merino-Barrero, Juan Andrés; Manzano-Sánchez, David; Valero-Valenzuela, Alfonso
The aims of this study were to uncover the different motivational climate profiles to compare differences on their implicit beliefs of sports ability, motivational orientation, and intention to be physically active, and finally to analyse the relationship of the gender with motivational climate profiles, in a large sample of high-performance handball players in Spain. A total of 444 (233 males, 211 females) high-performance handball players agreed to participate. They completed a questionnaire that included the Spanish validated versions of Perceived Motivational Climate in Sport Questionnaire, Conceptions of the Nature of Athletic Ability Questionnaire-2, Sport Motivation Scale and Intention to be Physically Active Questionnaire. A hierarchical cluster analysis uncovered two independent motivational climate profiles that were confirmed by a K-Means cluster analysis: "mastery climate" and "performance climate". The results revealed that the mastery climate profile comprised players with less amotivation and higher scores in both incremental ability belief and greater intention to be physically active, and more women than men. By contrast, the performance climate profile comprised players with higher scores in extrinsic motivation and amotivation, both entity ability belief, lower intention to be physically active and primarily men. The importance of the coach in creating a mastery climate that fosters athletes' engagement was confirmed.